2016
DOI: 10.1016/j.jshs.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional supplements use in high-performance athletes is related with lower nutritional inadequacy from food

Abstract: BackgroundThe use of nutritional supplements (NS) among athletes is widespread. However, little is known about the relationship between nutritional adequacy and NS usage. The aims of this study were to evaluate the NS usage and to compare the nutritional intake from food and prevalence of micronutrient inadequacy (PMI) between NS users and non-users.MethodsPortuguese athletes from 13 sports completed an NS usage questionnaire and a semi-quantitative food-frequency questionnaire assessing information over the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
36
2
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 36 publications
7
36
2
8
Order By: Relevance
“…However, herbal supplement usage gave rise from the present study ndings (13.5%) was very low than the predicted prevalence by the researchers. This observation collaborates with the previous ndings [4,27,28,22]. It shows that the although indigenous medicine system in Sri Lanka has introduced lot of herbal supplements to the local market, athletes less perceived need of them.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, herbal supplement usage gave rise from the present study ndings (13.5%) was very low than the predicted prevalence by the researchers. This observation collaborates with the previous ndings [4,27,28,22]. It shows that the although indigenous medicine system in Sri Lanka has introduced lot of herbal supplements to the local market, athletes less perceived need of them.…”
Section: Discussionsupporting
confidence: 90%
“…However, according to the reported literature, athlete performances have not merely increased due to supplements consumption while only a few have given the positive outcome [28]. Furthermore, many athletes used supplements without having an idea about their real bene ts.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, done by Monica Sousa et.al in 2016, the percentage of athletes using health supplements was 64%. (28) Another study done in the United States showed that 89% of adult athletes were using at least one supplement at the time of the study. (29) A study done by Ayman al jawadi in Saudi Arabia found that the prevalence of health supplement use was 37.8% (30) and a Lebanese study showed a prevalence of 36.3% among athletes.…”
Section: Discussion:-mentioning
confidence: 99%
“…La frecuencia de consumo de nutracéuticos fue en su orden: suplementos de vitaminas y minerales, suplementos dietarios, calcio y hierro (19,52,(54)(55)(56)(57)(58)(59).…”
Section: Prevalencia De Consumounclassified